Evaluation of self-care skills training and solution-focused counselling for health professionals in psychiatric medicine: a pilot study. (1st October 2016) - Mache, Stefanie; Bernburg, Monika; Baresi, Lisa; Groneberg, David A.
Abstract: Objective: The purpose of this pilot study was to implement and to evaluate a self-care skills training with solution-focused counselling to support psychiatrists in handling their daily work challenges. Methods: A total of 72 psychiatrists working in a psychiatric clinic were randomised in a single-blind trial to either an intervention group or a control group. Outcomes were measured at baseline and at the end of the training (follow-up 1: after 3 months; follow-up 2: after 6 months). A validated questionnaire including the Perceived Stress Questionnaire, the Copenhagen Psychosocial Questionnaire, Brief Resilient Coping Scale, Self-Efficacy Scale and the Quality of Relationship Inventory was used. Results: Psychiatrists in the intervention group reached a significant reduction in perceived job stress ( p  = 0.01, d  = 0.05), improvements in job satisfaction ( p  = 0.02, d  = 0.04), resilience ( p  = 0.02, d  = 0.04) and self-efficacy ( p  = 0.04, d  = 0.02) from baseline to all follow-ups with no comparable results seen in the control group. Psychiatrists stated an improved quality of physician–patient relationship (e.g. support, conflict management; p  < 0.05). Conclusions: A self-care skills training, including solution-focused counselling, for psychiatrists was associated with significant improvements in perceived stress, job satisfaction, individual protective skills and quality of relationship to patients. This training is suitable to implement as a group training program for psychiatrists.